Real Learning in a Virtual World: A Case Study of the School of Information Studies’ Learning Centre in Second Life / Lyn Hay and Bob Pymm - Hay, Lyn; Pymm, Bob (2011)
Following a review of the online delivery of distance education programs within the School of Information Studies (SIS) program at Charles Sturt University, a team of academics worked with an external consultant to design a purpose built SIS Learning Centre in Second Life (SL), a 3D virtual world environment in which people (via their avatars) may act as if in the ‗real‘ world. This paper discusses the design and implementation of a variety of teaching and learning activities in this virtual world environment, examining both student and faculty experiences throughout the teaching sessions, and exploring the affordances provided by the 3D virtual world of Second Life. Findings suggest that most students see this approach as providing a valuable opportunity to interact with each other and with faculty. For academics, the benefits provided by Second Life are acknowledged but the time commitment required to establish and manage the class in this virtual world need to be considered when adopting this approach.